Evaluation of wheat (Triticum aestivum) genotypes for productivity and economics under graded levels of nitrogen in temperate Kashmir - SINGH, PURSHOTAM; SINGH, PARMEET; SINGH, K N; SINGH, REKHI; AGA, F A; BAHAR, F; RAJA, WASEEM (The Indian Journal of Agricultural Sciences, 2010)
A study was conducted during winter seasons of 2005 and 2006 to find out the effective and economical rate of nitrogen for suitable genotypes of wheat (Triticum aestivum L. emend.Fiori and Paol.) under temperate conditions of Kashmir. The 4 wheat genotypes (‘VL738’, Shalimar ‘wheat 1’, ‘HS 240’ and ‘HS 365’) as influenced by 4 nitrogen levels (0, 50, 100 and 150 kg N/ha) were tested in a field experiment at Wadura. Genotype trend in grain yield ranged from 4.48 to 4.04 tonnes/ha in the order of ‘Shalimar Wheat 1’ > ‘HS 365’>‘HS 240’> ‘VL 738’. ‘Shalimar wheat 1’ recorded highest grain yield which is 10.8%, 13.7% and 5.77% more over ‘VL738’, ‘HS240’ and ‘HS365’, respectively. Nitrogen-use efficiency indices at 100 kg nitrogen application (i e agronomy efficiency, 17.6 kg/kg, physiological efficiency, 57.41 kg/kg and N recovery =31.2%) also showed superiority of ‘Shalimar wheat 1’ over other genotypes. The optimum dose of nitrogen worked out from response equation of genotypes were 115.31, 122.35, 119.61 and 122.89 kg/ha, respectively. Among all the treatment combinations. ‘Shalimar wheat 1’ applied with 100 kg N/ha was found more economic with benefit : cost ratio of 2.25 under temperate valley conditions.